STUDI TATA RUANG RUMAH ADAT “SIWALUH JABU” DESA LINGGA - Erwin Ardianto Halim (Jurnal Dimensi Seni Rupa dan Desain, 2020)
AbstractKaro traditional house is an authentic historical-cultural heritage and still stands tall. The existence of the Karo traditional house does not only function as an ordinary place to live, but has a meaning which is a medium of cultural expression of the people seen in the architecture and interior of this traditional karo house. This research is a study of spatial planning and its functions at this time. The results of the study know the spatial patterns in the traditional house of Siwaluh Jabu and find out what I am experiencing changes in the traditional house layout of Siwaluh Jabu. This has become very important in this research for the development of cultural history in the world of interior design education. AbstrakRumah adat Karo merupakan warisan sejarah-budaya yang otentik serta masih berdiri tegak. Keberadaan rumah adat Karo tidak saja berfungsi sebagai tempat tinggal biasa, namun memiliki makna yang merupakan media ekspresi kebudayaan masyarakatnya terlihat pada bentuk arsitektur dan interior rumah adat karo ini. Penelitian ini merupakan studi tata ruang dan fungsinya pada saat ini. Hasil penelitian mengetahui pola tata ruang pada rumah adat Siwaluh Jabu dan mengetahui apa saya yang menggalami perubahan pada tata ruang rumah adat Siwaluh Jabu. Hal tersebut menjadi sangat penting dalam penelitian ini untuk pengembangan ilmu sejarah budaya dalam dunia pendidikan desain interior.